Comparing quality of primary healthcare between public and private providers in China: study protocol of a cross-sectional study using unannounced standardised patients in seven provinces of China. Issue 1 (12th January 2021) - Xu, Dong; Pan, Jay; Dai, Xiaochen; Hu, Mengyao; Cai, Yiyuan; He, Hua; Zhang, Yaoguang; Liao, Jing; Chen, Yaolong; Gong, Wenjie; Zhou, Zhongliang; Zhang, Nan; et al.
Abstract : Introduction: The Chinese government has encouraged the development of private sector in delivering healthcare, including primary healthcare (PHC) in the new round of national health reform since 2009. However, the debate about the role of the private sector in achieving universal health coverage continues with poor support from theories and empirical evidence. This study intends to compare the quality of PHC services between the private and public providers in seven provinces in China, using unannounced standardised patients (USPs). Methods: We are developing and validating 13 USP cases most commonly observed in the PHC setting. Six domains of quality will be assessed by the USP: effectiveness, safety, patient centredness, efficiency, timeliness and equity. The USP will make 2200 visits to 705 public and 521 private PHC institutions across seven provinces, following a multistage clustered sample design. Using each USP-provider encounter as the analytical unit, we will first descriptively compare the raw differences in quality between the private and public providers and then analyse the association of ownership types and quality, using propensity score weighting. Ethics and dissemination: The study was primarily funded by the National Natural Science Foundation of China (#71974211, #71874116 and # 72074163) and was also supported by the China Medical Board (#16-260, #18-300 and #18-301), and have received ethical approval from Sun Yat-sen University (#2019–024). The validated USP tool and the data collected in this study will be freely available for the public after the primary analysis of the study. Trial registration number: Chinese Clinical Trial Registry: #ChiCTR2000032773.